Clinicopathologic Features of Facial Dermatofibromas, a Cohort Study, and a Systematic Review of Literature. (27th November 2022) - Alsawas, Mouaz; Dundar, Bilge; Prokop, Larry; Murad, M. Hassan; Swick, Brian
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: Dermatofibromas are common skin tumors that typically occur on the extremities and trunk and demonstrate benign behavior, frequent recurrences, and very rare metastasis. Facial dermatofibromas are rare and not well studied. We analyzed clinicopathologic features of facial dermatofibromas. Design: Considering the rarity of the condition, we conducted a cohort study and a systematic review. We queried medical records of a single tertiary care center for dermatofibromas from January 1, 2000, to July 1, 2021. A systematic review of multiple databases was conducted through October 27, 2021, to include studies reporting facial dermatofibromas. Random-effects meta-analysis was used to estimate pooled odds ratio and proportions with associated 95% confidence interval (CI). Results: The cohort study identified 2858 cases of dermatofibromas, of which, 23 cases from 18 patients were on the face (1%). The mean age was 52.7 ± 17.8 years. Fifty-six percent of the cases were women. The most common location was the forehead (6 cases). The mean follow-up was 54 months. Forty-four percent of the cases had subcutaneous involvement, and 39% were the cellular type. Margins were positive in 89% of the cases, recurrence rate was 22%, and no metastases were observed. The systematic review included 10 studies (119 patients). Meta-analyses showed that facial dermatofibromas were 2% of all dermatofibromas (95% CI: 1%–3%). The local recurrence rate was 14% (95% CI: 6%–26%). Facial dermatofibromas with subcutaneous involvement were more likely to recur [odds ratio 4.53 (95% CI: 1.12–18.24)]. Before histopathologic examination, clinical differential diagnosis included dermatofibromas in only 9% of the cases (95% CI: 2%–19%). Conclusion: Facial dermatofibromas are rare and are difficult to fully excise. Cellular type and subcutaneous or muscular involvement are common in these cases and tend to have higher local recurrence rate than other nonfacial dermatofibromas. Wider excisions might be necessary for complete excision.